2019
DOI: 10.1016/j.aott.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of asymptomatic dysplasia in parents of children with developmental hip dysplasia

Abstract: ObjectiveThe aim of this study was to investigate whether being the parents of children with developmental hip dysplasia (DDH) is a risk factor for asymptomatic dysplasia.MethodsAsymptomatic parents of children who were diagnosed with DDH were assessed for presence of dysplasia by examining their anteroposterior pelvis radiographs at the neutral position. Eighty-six hips of 43 participants were included in the study group and 98 hips of 49 participants were included in the control group. Presence of hip dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Kronenig et al and Pottie et al reported that the healthcare team should be aware of cultural differences and expectations during healthcare (1,12). Ethnic differences, geographic location and having a family history, and swaddling were risk factors for DDH (13)(14)(15). DDH was included in the national screening program country.…”
Section: Discussionmentioning
confidence: 99%
“…Kronenig et al and Pottie et al reported that the healthcare team should be aware of cultural differences and expectations during healthcare (1,12). Ethnic differences, geographic location and having a family history, and swaddling were risk factors for DDH (13)(14)(15). DDH was included in the national screening program country.…”
Section: Discussionmentioning
confidence: 99%
“…Although the AWh was deeper in patients aged >18 months (mean 1.3 cm) than in those aged 12–18 months (mean 1.2 cm) before CR, the improvement in AWh was greater in the latter group (mean improvement 1.4 vs. 1.3 cm). The majority of authors measured acetabular width by a line connecting the superolateral and inferomedial edges of the acetabulum ( 26 , 27 ). However, the inferomedial edge is not easily identified in radiographs from younger children.…”
Section: Discussionmentioning
confidence: 99%